Daily Spiritual Experiences Scale Psychometric Analysis among Argentinian Adolescents and Young Adults - Oñate, María Emilia (2022)
Objective. The present work aimed to evaluate the psychometric properties of the Daily Spiritual Experience Scale (DSES), specifically analyzing the internal consistency, the discrimination of the items, the exploratory and confirmatory factorial structure, and the constructive validity. Method. A sample of 692 adolescents and young adults aged between 12 and 28 years old was collected. In addition, the Daily Spiritual Experiences Scale and the emotional well-being dimension of the Multidimensional Flourishing Scale were applied. Results. Discriminatory items and good internal consistency were evidenced. The unifactorial structure was verified, and a correlation between spirituality and emotional well-being was found, which supports the construct’s validity. It is concluded that the DSES has adequate psychometric properties that support its use for the evaluation of spirituality in Argentine adolescents and young adults.